Ethical Review Challenges and Strategies in Cross-institutional and Interdisciplinary Collaborative Research Projects - Weiwei XU; Ming GAO; Ping JI (Yixue yu zhexue)
This study aims to discuss the new challenges posed by ethical review of scientific research activities. It systematically reviews relevant regulations concerning the ethical oversight of collaborative projects and draws on international advanced experiences. Based on current practice, the paper analyzes key issues, including ethical value conflicts across disciplines and institutions, uneven development of ethical review capacities, lack of detailed ethical guidelines for cutting-edge technologies, and unclear processes and responsibilities in institutional ethical reviews. The existing review criteria, models, quality, and efficiency of reviews all need improvement. The study proposes suggestions for ethical review models tailored to collaborative research, emphasizing that effective ethical oversight in cross-institutional and interdisciplinary projects depends on coordinated governance among stakeholders. Key strategies include strengthening ethical guidelines, enhancing internal institutional governance, improving inter-institutional coordination, and increasing government support.